Key Safety Rules During Safety Investigation – On The Example of Two International Organisations - Malgorzata KOCHANOWICZ (Communications of International Proceedings, 2023)
The aim of the work is to look at the most important safety principles during the investigation of aviation accidents. Two international organisations dealing with civil aviation were selected to present the topic. The most important legal acts in the field of investigation of aviation occurrences issued by these organizations were analyzed. The most important safety principles were selected from these acts and then compared.
Keywords: international organisation; safety investigation; safety; accident; incident